2012
DOI: 10.12659/msm.882202
|View full text |Cite
|
Sign up to set email alerts
|

Attentional and emotional functioning in schizophrenia patients treated with conventional and atypical antipsychotic drugs

Abstract: SummaryBackgroundEffectiveness of antipsychotics in treating emotional and cognitive deficits in schizophrenia still remains controversial. The aim of our study was to assess emotional and cognitive functioning in schizophrenic inpatients currently treated with typical antipsychotics (perphenazine, perazine, fluphenazine, and haloperidol) and in another group of schizophrenic inpatients currently on atypical antipsychotics (olanzapine, risperidone, amisulpride, and quetiapine).Material/MethodsOne hundred patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…All patients were medicated with antipsychotics at the time of evaluation; however, available evidence suggests a positive influence of atypical antipsychotics in attentional processes, improving deficits already present in untreated first-episode patients (e.g., Keedy et al, 2015;Kucharska-Pietura et al, 2012). Further studies should also control for effects of medication.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were medicated with antipsychotics at the time of evaluation; however, available evidence suggests a positive influence of atypical antipsychotics in attentional processes, improving deficits already present in untreated first-episode patients (e.g., Keedy et al, 2015;Kucharska-Pietura et al, 2012). Further studies should also control for effects of medication.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found an association between affective or overall empathy and negative symptoms (Bora et al, 2008;Kucharska-Pietura et al, 2012;Lincoln et al, 2011;Shamay-Tsoory et al, 2007;Smith et al, 2014;Sparks et al, 2010); associations have also been found with positive symptoms (Konstantakopoulos et al, 2014;Lysaker et al, 2013;Smith et al, 2014;Sparks et al, 2010), depression (Abramowitz et al, 2014;Didehbani et al, 2012;Horan et al, 2015), anxiety (Achim et al, 2011), and insight (Didehbani et al, 2012;Lysaker et al, 2013;Pijnenborg et al, 2013). However, though several studies report significant relationships with symptoms, as many studies have reported no association (Corbera et al, 2013;Derntl et al, 2012a;Derntl et al, 2012b;Fresán et al, 2015;Fujino et al, 2014;Fujiwara et al, 2008;Lam et al, 2014;Lehmann et al, 2014;McCormick et al, 2012;Montag et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, when comparing chronically ill people with schizophrenia to healthy controls, only two of the 22 studies that examined sex differences provided evidence that women with schizophrenia outperform men on FEP tasks. From our PubMed search of more recent studies not included in the meta-analyses, a total of 16 of the 20 studies that examined adults with chronic schizophrenia either did not report on sex differences or controlled for sex in their FEP analyses [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] , with one study including an all-male sample [68] . Of the remaining four studies, three studies did not find sex differences on an FEP identification task [69][70][71] .…”
Section: Adults With Chronic Schizophreniamentioning
confidence: 99%